Analisis Kemampuan Berpikir Calon Guru dalam Menyelesaikan Permasalahan Matematika Berorientasi pada HOTS - Maimunah Maimunah; Finata Rastic Andrari; Nurmala Dewi Qadarsih (Universitas Indraprasta PGRI Jakarta, 2020)
Mathematics is one of the sciences that plays an important role in the development of science, technology, and the advancement of human thinking, starting from the basic education level to the higher education level so that students are ablet to think logically, systematically, analytically, critically, creatively and have the ability to work together. Mathematics Education students, as prospective teachers, are expected to be able to solve problems that measure HOTS in advance so that later they can help students solve the HOTS questions. This study aims to describe the thinking skills of prospective teachers in solving HOTS-oriented math problems. The type of research used was descriptive qualitative with 3 subjects from the fifth-semester students of Mathematics Education Unindra PGRI consisting of subjects in the low, medium, and high groups, each represented by 1 person. The data analysis techniques used were data reduction, categorization, synthesis, and the preparation of working hypotheses. The results showed that the prospective teachers were able to solve HOTS-oriented problems at the level of analyzing and evaluating. Of the three research subjects, the three subjects were able to meet the level indicators of analyzing and evaluating quite well. At the creative level, only one teacher candidate was able to meet 2 of the 4 existing creative indicators. Meanwhile, the other 2 prospective teachers were only able to meet 1 of the 4 creative level indicators.